The Export Industrial Subsidies in the Regions of the Russian Federation: their Characteristic and WTO Compliance - Elena Vasilyevna Zhiryaeva; Alina Aleksandrovna Maslova (Управленческое консультирование)
Export of hi-tech and some other large enterprises, and also small and medium-sized enterprises is supported at the regional level in the Russian Federation. As regards to small and medium sized enterprises co-financing from the federal budget makes 50-80%. There is a standard tool kit of export help for SME which can be expanded at subnational level. Export support program of the Leningrad and Rostovregionas well as programs for SME havea form of export subsidy from WTO point of view.